ECG Adapted Fastest Route Algorithm to Localize the Ectopic Excitation Origin in CRT Patients - Potyagaylo, Danila; Chmelevsky, Mikhail; van Dam, Peter; Budanova, Margarita; Zubarev, Stepan; Treshkur, Tatjana; Lebedev, Dmitry (Frontiers in Physiology, 2019)
Although model-based solution strategies for the ECGI were reported to deliver promising clinical results, they strongly rely on some a priori assumptions, which do not hold true for many pathological cases. The fastest route algorithm (FRA) is a well-established method for noninvasive imaging of ectopic activities. It generates test activation sequences on the heart and compares the corresponding test body surface potential maps (BSPMs) to the measured ones. The test excitation propagation patterns are constructed under the assumption of a global conduction velocity in the heart, which is violated in the cardaic resynchronization (CRT) patients. In the present work, we propose to apply the dynamic time warping (DTW) to the test and measured ECGs before measuring their similarity. The warping step is a non-linear pattern matching that compensates for local speed-ups and delays in the temporal sequences, while aligning them in an optimal way with respect to a distance function. To evaluate benefits of the temporal warping for FRA-based BSPMs, we considered three scenarios. In the first setting, a simplified simulation example was constructed to illustrate the temporal warping and display the resulting distance map. Then, we applied the proposed method to eight BSPMs produced by realistic ectopic activation sequences and compared its performance to FRA. Finally, we assessed localization accuracy of both techniques in ten CRT patients. For each patient, we noninvasively imaged two paced ECGs: from left- and rightventricular implanted leads. In all scenarios, FRA-DTW outperformed FRA in terms of localization accuracy. For the clinical cases, the distance errors were reduced from 16 (8-23) mm to 5 (2-10) mm for all pacings, from 15 (11-25) mm to 8 (3-13) mm in the left, and from 19 (6-23) mm to 4 (2-8) mm in the right ventricle, respectively. The obtained results suggest the ability of temporal ECG warping to compensate for an in-homogeneous conduction profile, while retaining computational efficiency intrinsic to FRA.